Kidney injury molecule-1: A potential marker of renal recovery after laparoscopic sleeve gastrectomy - Rania Khalil; Hosam Elghadban; Moustafa Abdelsalam; Mona Tawfik (The Korean Society of Nephrology, 2020)
Background : Bariatric surgeries were reported to improve diabetes and hypertension; however, the effect on renal recovery has not been fully explored. The aim of this study was to evaluate the effect of laparoscopic sleeve gastrectomy (LSG) in morbidly obese patients on renal function, degree of albuminuria, and kidney injury molecule-1 (KIM-1) level. Methods : This was a prospective observational study conducted at Mansoura University Hospitals from January to June 2017. Forty-four morbidly obese patients (29 females and 15 males) who met the 1991 WHO criteria for obesity surgery were included. Patients underwent surgical LSG for treatment of morbid obesity, and all were followed for 6 months after surgery. Demographic, clinical, and laboratory data were collected and compared before and after surgery. Primary endpoints were the differences of albuminuria, estimated glomerular filtration rate (eGFR) and serum KIM-1 between baseline (pre-surgery) and 6-month post-surgery values. Results : Six-month post-surgery data showed significant reduction of body mass index, HbA1c, microalbuminuria, and serum KIM-1, and a significant increase in eGFR (all, P < 0.001). The serum KIM-1 level positively correlated with microalbuminuria and serum creatinine (r = 0.596, P = 0.001 and r = 0.402, P = 0.034, respectively). Postoperative data showed that patients with microalbuminuria had significantly lower eGFR and higher KIM-1 values than those without microalbuminuria (P = 0.003 and 0.049, respectively). Conclusion : We showed potential benefits of LSG against obesity-associated kidney damage. This is evidenced by improving eGFR and reducing levels of both KIM-1 and microalbuminuria. The serum level of KIM-1 may be a potential marker for renal recovery after LSG.